2017
DOI: 10.1002/ajh.24917
|View full text |Cite
|
Sign up to set email alerts
|

Utility and limitations of exome sequencing in the molecular diagnosis of pediatric inherited platelet disorders

Abstract: Inherited platelet disorders (IPD) are a heterogeneous group of rare disorders that affect platelet number and function and often predispose to other significant medical complications. In spite of the identification of over 50 IPD disease-associated genes, a molecular diagnosis is only identified in a minority (10%) of affected patients without a clinically suspected etiology. We studied a cohort of 21 pediatric patients with suspected IPDs by exome sequencing (ES) to: (1) examine the performance of the exome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…14 Next generation sequencing (NGS) has enhanced diagnostic capabilities, but causal variants often remain uncharacterized. 15 These disorders may not be diagnosed until an invasive procedure causes excessive bleeding, or may be misdiagnosed as autoimmune unless additional affected family members are identified. 16 Because platelet-related genes can be associated with increased risk of myelodysplastic syndrome (MDS), malignancy, bone marrow failure, cardiac arrhythmias, cataracts, deafness, or renal failure, molecular characterization is important for defining prognosis and guiding clinical decisions.…”
mentioning
confidence: 99%
“…14 Next generation sequencing (NGS) has enhanced diagnostic capabilities, but causal variants often remain uncharacterized. 15 These disorders may not be diagnosed until an invasive procedure causes excessive bleeding, or may be misdiagnosed as autoimmune unless additional affected family members are identified. 16 Because platelet-related genes can be associated with increased risk of myelodysplastic syndrome (MDS), malignancy, bone marrow failure, cardiac arrhythmias, cataracts, deafness, or renal failure, molecular characterization is important for defining prognosis and guiding clinical decisions.…”
mentioning
confidence: 99%
“…For gene panels, individual genes have differing levels of evidence of clinical validity. 2426 With the exception of the gene pairs CYP2C9 / VKORC1 for warfarin and CYP2C9 / HLA-B for phenytoin (brand name Dilantin), all of the CPIC guidelines focus on a single gene-drug or gene–drug class interaction. The combined effect of variations in multiple genes relevant to a given medication remains largely unknown, though some test developers have suggested that combinatorial PGx testing, including genes involved in pharmacokinetic and pharmacodynamic pathways, may provide a more comprehensive prediction of drug response by using proprietary algorithms to predict drug safety 27 and may reduce medication costs.…”
Section: Discussionmentioning
confidence: 99%
“…However, interpretation of genetic findings can be difficult especially in patients without a peculiar clinical picture. In fact, NGS usually detects many variants of unknown or uncertain significance, whose correlation with the patient's phenotype is unresolved, and over-interpretation is a major risk [73][74][75][76][77]. Data from big case series reported so far indicated that NGS is able to achieve a diagnosis in nearly 50% of IPD patients suffering from congenital thrombocytopenia, and in nearly 25% of those with inherited platelet function disorder.…”
Section: Current Diagnostic Tools For Ipdsmentioning
confidence: 99%